1991
DOI: 10.1136/thx.46.8.549
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prevalence of reversible airways obstruction in rural and urban Zimbabwean children.

Abstract: The prevalence of reversible airways obstruction has been assessed in children in three areas in Zimbabwe-northern Harare (high socioeconomic class urban children), southern Harare (low socioeconomic class urban children), and Wedza Communal Land (rural children from peasant families). Peak expiratory flow (PEF) was measured before and after six minutes' free running in 2055 Zimbabwean primary school children aged 7-9 years. Height and weight were measured and nutritional state expressed as a percentage of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
2
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(99 citation statements)
references
References 21 publications
4
87
2
6
Order By: Relevance
“…Using a similar free running test in children, the prevalence of exercise-induced bronchoconstriction varies from 12% in children aged 12 yrs from New Zealand [25] to 6% in children aged between 7-16 years in Copenhagen [9]. However, an extremely low prevalence of 0.1% has been reported in a rural area of Zimbabwe [26]. Although the presence of such marked variations strongly suggests that the environment influences both asthma and bronchial responsiveness, the influence of genetic factors is also possible at this wide geographical scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a similar free running test in children, the prevalence of exercise-induced bronchoconstriction varies from 12% in children aged 12 yrs from New Zealand [25] to 6% in children aged between 7-16 years in Copenhagen [9]. However, an extremely low prevalence of 0.1% has been reported in a rural area of Zimbabwe [26]. Although the presence of such marked variations strongly suggests that the environment influences both asthma and bronchial responsiveness, the influence of genetic factors is also possible at this wide geographical scale.…”
Section: Discussionmentioning
confidence: 99%
“…Since reduction in PEFR due to fatigue was not studied by BARDAGÍ et al [15], it is not known whether differences in the prevalence of bronchial responsiveness after running between the present study and that of BARDAGÍ et al [15] may be attributed to the previously mentioned fatigue effect. In Zimbabwean children, the prevalence of exerciseinduced bronchoconstriction varied from 5.8% in an urban area with high living standards to 0.1% in a rural district [26]. Different prevalence rates in populations with a similar genetic background are illustrated by studies in Barcelona and Mataró [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is most likely that the lower prevalence of allergy seen in children from hand dishwashing families is related to lifestyle factors, but lifestyle factors other than dishwashing practices may be important. For example, overcrowded housing, 20 low socioeconomic status, 28,29 and immigration status 30 are all factors that have been associated with reduced allergy levels in various studies, and these factors may also be associated with dishwashing practices. We used multivariate OPLS analyses to screen the data for confounders and covariates, but despite adjusting for such factors in logistic regression models, the associations between hand dishwashing and allergy, and traditional cooking and allergy, remained, implying that a causal relationship might be possible.…”
Section: Figurementioning
confidence: 99%
“…The finding of Keeley et al, that the prevalence of BHR was similar in different race groups of the same socio-economic status, questions the race-based conclusions of previous authors [4]. On the other hand, Terblanche et al found that the prevalence of exercise-induced bronchoconstriction was significantly higher among white children living in Cape Town (5.87%) than in coloured children resident there (4.05%).…”
Section: Prevalence Of Asthma In Southern Africamentioning
confidence: 85%